HIGH-TEMPERATURE STEAM AND AIR OXIDATION OF CHROMIUM-COATED OPTIMIZED ZIRLO™ - Gauthier Bourdon; Martin Ševecek; Jakub Krejčí; Ladislav Cvrček (Acta Polytechnica CTU Proceedings)
The presented study focuses on Cr-coated cladding material and its oxidation performance in high-temperature steam and air. As the substrate material, Optimized ZIRLO™ was used which was coated by chromium using unbalanced magnetron sputtering. The experimental methods are described and the presented results focus mainly on weight gain and oxidation kinetic evaluation. The experiments were carried out in the high-temperature range between 1000 and 1300 °C. The test conditions focus mainly on the air oxidation tests that are relevant for some of severe accidents with air ingress and have not yet been studied in detail and are not available in literature. These data are supported with steam oxidation data to directly compare the kinetics in two different oxidizing environments.